Tribology And Electrochemical Behavior Of Electroless Quaternary Nickel Alloy Deposition For Cutting Tools - Mohamad Noor, Mohamad Noor Azran (2019)
Coating on steel can improve various characteristics such as corrosion resistance in salt water, surface hardness and wear resistance. One of the coating methods is electroless deposition using reducing agent to reduce metal ion onto substrate. Electroless nickel deposition using hypophosphite as reducing agent can produce a binany Ni-P alloy that has superior properties than Ni itself. Furthermore, the formation of quaternary Ni alloy can be produced by adding other metal ions such as Co, Cu, Zn, and W. The addition of Cu in the Ni-P alloy matrix improves the corrosion resistance in salt water by increasing its barrier resistance and also surface properties. Co addition provides the passive film formation while retaining the corrosion potential in salt water at noble potential compare to steel. However, the effect of Cu and Co ions addition in hypophosphite based electroless Ni bath on its quaternary Ni alloy formation, mechanism and its properties is still less known. In this work, electroless Ni-Co-Cu-P alloy deposit on steel was produced using hypophosphite base electroless Ni plating bath by adding cobalt and copper salts into the plating bath solutions. The effect of cobalt and copper addition on the surface morphology, hardness, and elemental composition of nickel alloy deposition rate was investigated via analysis with a Scanning Electron Microscope (SEM), microVickers Hardness Tester and X-ray Fluorescence (XRF) respectively. Coefficient of friction and wear rate of the coating was studied and analyzed using Pin-on-Disk test. Corrosion behavior of electroless quaternary Ni alloy deposit was studied using polarization curve measurements in a classical three electrode configuration using the coating surface as a working electrode, graphite as a counter electrode and Ag/AgCl/KCl(saturated) as a reference electrode. Besides that, the reaction mechanism is analyzed using cyclic voltammetry measurement using graphite as both counter and working electrode.The electroless quaternary Ni alloy with Cu, Co and P alloying element has been suscessfully done in both alkaline and acidic bath. The Co is easily deposited in alkaline bath while Cu in acidic bath based on XRF result. The corrosion behavior of Ni-Co-Cu-P from pH 9.5 bath has the most excellent corrosion resistance behavior in salt solution that is 14.21 mm per year due to more noble corrosion potential and passive film potential compare to Ni-Cu-Co-P alloy and steel. Highest Co content in the Ni-Co-Cu-P alloy that is 5.79 wt% exhibit the highest hardness 991.3 HV compare to other Ni alloy compositions as well as Ni-W-P alloy. Nevertheless, the coefficient friction of the quaternary Ni alloy with higher Cu content (Ni-Cu-Co-P) is lower that Ni-Co-Cu-P alloy.